O potencial hidrogeniônico (ph) como parâmetro indicador do uso abusivo do aditivo alimentar fosfato em pescado - Lemos, Lyzandra Lais de Almeida (Universidade Federal Rural do Semi-Árido, 2017)
Considering the abusive use of humectant agents in frozen seafood processing, and a possible relationship between the pH parameter and the phosphate food grade additive, the objective of the present study was to evaluate if there is a correlation between the pH of the tuna meat and different concentrations and time of contact of food additive phosphate. The tuna fillets (average of 225 g) were immersed in cold solutions (5°C) of sodium tripolyphosphate (STPP) and phosphates blend (concentrations) at concentrations of 3, 5 and 10% (fillet:solution ratio of 1: 1; w:v) at 30, 60 and 120 minutes. Water was used as the control group. After immersion, the samples were drained, weighed (yield calculation), frozen in ultrafreezer (-35ºC for 24 h) and stored (-35ºC) for 15 days. After this period, the samples were thawed (5°C, 24 hours), drained for 5 minutes, and weighed (yield calculation). After thawing, samples were grilled (200°C for 3 minutes on each side) and weighed (yield calculation). Samples were withdrawn after each step (immersion, thawing and cooking) and submitted to pH, phosphate (P2O5) moisture and protein analysis. The yield (gain and loss weight) was determined by the weight of the samples before and after the treatments (immersion, thawing and cooking). All food additives used in the present study (STPP and Blend) demonstrated their efficacy in water retention after immersion, thawing and cooking. There was a gradual increase in moisture content (after immersion in solutions of STPP and Blend), and a consequent increase in moisture/protein ratio suggesting a new parameter to be considered as indicative use of humectant agents in seafood. There was a gradual increase in pH and residual phosphate (P2O5) in all treatments, and still remained below the limits established by national (pH) and international (P2O5) legislation. A linear correlation was observed between pH and P2O5 values, which may become a parameter to be considered as indicative use of humectant agents (phosphates) in seafood. From the results of experiments, we suggest a critical review on the current issue, and those possible changes can be evaluated in the official parameters as indicators of abusive use of the phosphate additive in seafood and to combat economic fraud in the frozen products. It should be emphasized that these suggestions should be the focus of the collaborative study for its validation
The hydrogenation potential (ph) as a parameter indicator of the abusive use of the feed additive phosphate in fish
Keywords: Pescado; Aditivos umectantes; Fraude; Retenção de água; Seafood; Humectant additives; Fraud; Water retention; CIENCIAS AGRARIAS::MEDICINA VETERINARIA